2021
DOI: 10.1101/2021.03.02.433514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient beta activity and connectivity during sustained motor behaviour

Abstract: Neural oscillations are thought to play a central role in orchestrating activity states between distant neural populations. In humans, long-range neural connectivity has been particularly well characterised for 13-30 Hz beta activity which becomes phase coupled between the motor cortex and the contralateral muscle during isometric contraction. Based on this and related observations, beta activity and connectivity have been linked to sustaining stable cognitive and motor states, or the "status quo", in the brai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…Moreover, the significant β activity in the CST identified during EEG β bursting events suggested that β bursts in the MU overlapped with those present at the cortical level. This confirms previous observations made using surface EMG signals ( Echeverria-Altuna et al, 2021 ). In addition, we observed that the common input inside the β range to the MU pool was of bursting behavior and appeared to be time-locked to cortical β bursts.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, the significant β activity in the CST identified during EEG β bursting events suggested that β bursts in the MU overlapped with those present at the cortical level. This confirms previous observations made using surface EMG signals ( Echeverria-Altuna et al, 2021 ). In addition, we observed that the common input inside the β range to the MU pool was of bursting behavior and appeared to be time-locked to cortical β bursts.…”
Section: Resultssupporting
confidence: 93%
“…One possible explanation would be that subjects were able to recruit larger cortical networks involved in the projection of β activity to the muscle. It was previously shown that the duration of β bursts was not affected by the performed motor task in normal conditions ( Echeverria-Altuna et al, 2021 ). Here, we observed, although not always significant, slightly longer periods of β events during β up-modulation compared with down-modulation of MU β.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These variations in burst probability are reflected in the slow changes in average spectral power (Feingold et al, 2015; Howe et al, 2011; Little et al, 2019; Rayson et al, 2022; Sherman et al, 2016), but suggest that single trial beta activity is more dynamic than classically thought. The rate and timing of single-trial beta events are tightly linked to behavior (Diesburg et al, 2021; Echeverria-Altuna et al, 2021; Enz et al, 2021; Feingold et al, 2015; Haufler et al, 2022; Heideman et al, 2020; Howe et al, 2011; Karvat et al, 2020; Khawaldeh et al, 2020; Kosciessa et al, 2020; Law et al, 2022; Little et al, 2019; Sherman et al, 2016; Shin et al, 2017; Sporn et al, 2020; Torrecillos et al, 2018; Walsh et al, 2022; Wessel, 2020; West et al, 2022), and are more predictive of response time and accuracy than average beta amplitude (Enz et al, 2021; Little et al, 2019). This shift in perspective from trial-averaged beta power to transient burst events has thus allowed for more fine-grained analyses of their relationship to behavior, but the functional role of beta bursts themselves is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, both cortical beta power and corticomuscular coherence are physiologically elevated, and this may have prevented these measures to be further enhanced by TACS given at beta. Given the large fluctuations that beta activity presents in the corticospinal system during sustained contractions (Echeverria-Altuna et al, 2021;Torrecillos et al, 2014), we consider that this factor should not have a major effect on our results.…”
Section: Discussionmentioning
confidence: 97%